Creative precarity - Uršič, Matjaž (Annales. Series historia et sociologia, 2018)
Along with the growth of creative economies, one can observe the phenomenon of increasing precarious work, which follows young individuals engaged in creative activities. The working process of creative individuals is very flexible in terms of schedules, place of work, and payment. As such, they often do not belong to the traditional (i.e., economically and socially stable) employment setup, which was usually organized around huge firms or institutions in the public sector. Instead, they tend to self-employ and quickly move from project to project, assignment to assignment, and job to job. Although some have described this as a type of desirable ever-changing lifestyle, such a work profile could be also described as precarious self-employment: a condition of existence without predictability or security, affecting material and/or psychological welfare. On the one hand, their work offers freedom, independence, and creative space, but it also has possible side effects manifested in a decrease in social security and an increase in stress due to work overload. Based on employment and wage statistics, this article analyzes fluctuations and changes in the social status of specific groups of creative workers in Slovenia and South Korea. It is assumed that intense employment restructuring points to the growing global trend of precarious working relations in the creative sector.
Keywords: Delovni pogoji; fleksibilno zaposlovanje; kreativna dejavnost; kreativni poklici; Precarious employment; Prekarno delo; Working conditions